СТАДІЇ БЮДЖЕТНОГО ПРОЦЕСУ НА МІСЦЕВОМУ РІВНІ ТА ОЦІНКА ЙОГО ЕФЕКТИВНОСТІ - Деніс, Олександр Володимирович (SUPREMANCE OF LAW, 2018)
Summary. The article reveals the content of the budget process stages at the local level in Ukraine. For this purpose: the drafting of budgets, drafting and adoption of the law on the State Budget of Ukraine (decision on the local budget); implementation of the budget, including amendments to the law on the State Budget of Ukraine (decision on the local budget); preparation and review of the report on the implementation of the budget and decision on it. The paper also identifies the effectiveness of the implementation of the budget process on the basis of the analysis of the budget legislation of Ukraine. The article analyzes four stages of the budget process at the local level and assesses its effectiveness.